Trust What You Hear : Policy Communication, Expectations, and Fiscal Credibility - End, Nicolas (IMF Working Papers; Working Paper, 2022)
How do policy communications on future f iscal targets af fect market expectations and beliefs about the future conduct of f iscal policy? In this paper, we develop indicators of f iscal credibility that quantify the degree to which policy announcements anchor expectations, based on the deviation of private expectations f rom official targets, for 41 countries. We find that policy announcements partly re-anchor expectations and that f iscal rules and strong fiscal institutions, as well as a good policy track record, contribute to magnifying this effect, thereby improving fiscal credibility. Conversely, empirical analysis suggests that markets reward credibility with more favorable sovereign financing conditions.